A marine analgesic peptide, Contulakin-G, and neurotensin are distinct agonists for neurotensin receptors: uncovering structural determinants of desensitization properties - Lee, Hee-Kyoung; Zhang, Liuyin; Smith, Misty D.; Walewska, Aleksandra; Vellore, Nadeem A.; Baron, Riccardo; McIntosh, J. Michael; White, H. Steve; Olivera, Baldomero M.; Bulaj, Grzegorz (Frontiers in Pharmacology, 2015)
Neurotensin receptors have been studied as molecular targets for the treatment of pain, schizophrenia, addiction, or cancer. Neurotensin (NT) and Contulakin-G, a glycopeptide isolated from a predatory cone snail Conus geographus, share a sequence similarity at the C-terminus, which is critical for activation of neurotensin receptors. Both peptides are potent analgesics, although affinity and agonist potency of Contulakin-G toward neurotensin receptors are significantly lower, as compared to those for NT. In this work, we show that the weaker agonist properties of Contulakin-G result in inducing significantly less desensitization of neurotensin receptors and preserving their cell-surface density. Structure-activity relationship (SAR) studies suggested that both glycosylation and charged amino acid residues in Contulakin-G or NT played important roles in desensitizing neurotensin receptors. Computational modeling studies of human neurotensin receptor NTS1 and Contulakin-G confirmed the role of glycosylation in weakening interactions with the receptors. Based on available SAR data, we designed, synthesized and characterized an analog of Contulakin-G in which the glycosylated amino acid residue, Gal-GalNAc-Thr10, was replaced by memantine-Glu10 residue. This analog exhibited comparable agonist potency and weaker desensitization properties as compared to that of Contulakin-G, while producing analgesia in the animal model of acute pain following systemic administration. We discuss our study in the context of feasibility and safety of developing NT therapeutic agents with improved penetration across the blood-brain barrier. Our work supports engineering peptide-based agonists with diverse abilities to desensitize G-protein coupled receptors and further emphasizes opportunities for conotoxin as novel pharmacological tools and drug candidates.